Application of Anticorrosive Coatings based on Modified English Kaolin and Epoxy Compound and Efficiency Evaluation based on the Development of a Mathematical Process Model - Gavhar, Miradullaeva (International Journal of Psychosocial Rehabilitation, 2020)
The article presents the results of research on the development of compositions of Organo mineral materials for the protection of metal parts of technological machines and structures working mainly under the influence of electrochemical mechanism of the corrosion process. The compositions of modified organomineral materials for anticorrosive coatings with the use of micro- and nanoscale particles of layered silicates (mineral fillers) are offered. To assess the reliability of experimental studies, mathematical processing was carried out with the use of the interpolation function of Lagrange for polarization resistance from time to time in 98% H2SO4solution.